Acute ischemia of the lower limb in a patient with infective endocarditis under the mask of coronavirus infection - I. P. Mikhaylov; V. A. Arustamyan; B. V. Kozlovskij; E. V. Kungurcev (Вестник хирургии имени И.И. Грекова, 2021)
Despite the fact that significant success has been achieved in the treatment of patients with infective endocarditis (IE), difficulties in clinical practice arise in the diagnosis of this disease. The article analyzes a clinical case of successful treatment of a patient with acute ischemia of the lower extremity due to thromboembolic syndrome in IE, the diagnosis of which was initially regarded as COVID-19. The clinical case occurred during the coronavirus infection (COVID-19) pandemic, and all patients who initially complained of fever were regarded as potentially infected, which, with insufficient examination, masked the clinical picture of infective endocarditis.